A legal analysis of the liabilities for wrongful disclosure of private informations by credit reporting agencies / Razian Abdul Rahim ... [et al.] - Abdul Rahim, Razian; Amir, Muhammad Hanif; Mohd Zaini, Muhammad Zulhairi; Noorazlan Ong, Noorazrein; Ahmad Zakaria, Shahril Amirul (2011)
On May 2010, Malaysia for the first time had a law regarding personal data protection which is the Personal Data Protection Act 2010 (PDPA). On the other hand, the Credit Reporting Agencies (CRAs) which carry credit reporting businesses are control and regulated by the Credit Reporting Agencies Act 2010 (CRAA). We had carried out a study on the law and regulations on privacy regarding personal data and analyzed the extent of protection, rights and remedies given to the victim of the CRAs under the CRAA. The scope of this study focuses on the applicability of the law regarding personal data protection for the people from the CRAs in Malaysia. This paper analyses and evaluates how the CRAs acquire the information and how can it being disclosed. It also looks at the penalties and remedies that may be acquired by the people if the CRAs had misused their information or gave false or outdated information. The objectives of this study are to critically study the extent of the protection and rights of privacy which is provided under the CRAs, significantly analyze the remedies for the victims of CRAs and to propose any recommendations or amendment to the CRAs in order to improve the protection for an individual.